Forecasting the Influence of Climate Change on Agroecosystem Services: Potential Impacts on Honey Yields in a Small-Island Developing State - Diana L. Delgado; María Eglée Pérez; Alberto Galindo-Cardona; Tugrul Giray; Carla Restrepo (Psyche: A Journal of Entomology)
Global change poses numerous challenges to developing nations and small-island developing states (SIDSs). Among these are the effects of climate change on honeybees’ provisioning services including honey production. Here we ask two questions. First, what is the relationship between honey yield and climate in a tropical environment? Second, how does yield vary spatially under current climate and future scenarios of climate change? Focusing on the island of Puerto Rico, we developed an ensemble of bioclimatic models that were used in a geographical information system to identify suitable areas for honey production under current and future scenarios of climate change. A comparison between contemporary (1998–2005) and historical (1910–1974) honey yield data revealed a reduction in average yield, including variability, over time, with current yields averaging 5.3 L/colony. Three bioclimatic variables were retained by at least three models: temperature seasonality and mean temperature of the wettest quarter were negatively correlated with honey yields whereas precipitation of the wettest month was positively correlated. The four models varied in terms of their predictions but showed that both honey yields and areas suitable for honey production will decrease under scenarios of climate change. These results illustrate the possible impacts of climate change on honey and ultimately honeybees.